2010
DOI: 10.1007/s11671-010-9526-0
|View full text |Cite
|
Sign up to set email alerts
|

Nanodiamonds as Carriers for Address Delivery of Biologically Active Substances

Abstract: Surface of detonation nanodiamonds was functionalized for the covalent attachment of immunoglobulin, and simultaneously bovine serum albumin and Rabbit Anti-Mouse Antibody. The nanodiamond-IgGI125 and RAM-nanodiamond-BSAI125 complexes are stable in blood serum and the immobilized proteins retain their biological activity. It was shown that the RAM-nanodiamond-BSAI125 complex is able to bind to the target antigen immobilized on the Sepharose 6B matrix through antibody–antigen interaction. The idea can be extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 22 publications
0
61
0
3
Order By: Relevance
“…4 F-NDP as a platform are capable of diverse functionalization and have been coupled to antibodies for protein detection, adsorbed with small molecules for therapeutic purposes, and even inorganically doped for use as catalysts. [5][6][7] Our previous set of in vitro studies, in which we demonstrated the specific association of the F-NDP NVN -Bit with platelets embedded within plasma clot generated by thrombin-activated rat platelet-rich plasma, provided a first-line "proof of feasibility" for our concept. 4 Since transmission of light across biological tissues is subject to interferences (scatter, absorption, diffraction) by organic and inorganic materials of the tissues, 8 we have primarily focused on the near-infrared (NIR) optical window, which significantly facilitates penetration of light through biological tissues.…”
mentioning
confidence: 82%
“…4 F-NDP as a platform are capable of diverse functionalization and have been coupled to antibodies for protein detection, adsorbed with small molecules for therapeutic purposes, and even inorganically doped for use as catalysts. [5][6][7] Our previous set of in vitro studies, in which we demonstrated the specific association of the F-NDP NVN -Bit with platelets embedded within plasma clot generated by thrombin-activated rat platelet-rich plasma, provided a first-line "proof of feasibility" for our concept. 4 Since transmission of light across biological tissues is subject to interferences (scatter, absorption, diffraction) by organic and inorganic materials of the tissues, 8 we have primarily focused on the near-infrared (NIR) optical window, which significantly facilitates penetration of light through biological tissues.…”
mentioning
confidence: 82%
“…Their feasibility of applications due to their biocompatibility and high temperature resistant, make them an interesting matrix for the development of new low-dimensional carbon nanomaterials [25,26,66].…”
Section: Intermatrix Synthesis Cds-qds In Nanodiamonds (Cds-qds@nds)mentioning
confidence: 99%
“…Nanodimonds (NDs) [23] , [24,25], which is other carbon nanoallotrope, exhibit interesting mechanical and optical properties, high surface areas and tuneable surface structures [25]. Moreover, they are non-toxic, which makes them suitable to biomedical applications, a feasible alternative as nanocarriers for addressed delivery of drugs and biolabeling [26], [27].…”
Section: Introductionmentioning
confidence: 99%
“…Only in few cases the nuclear localization of NDs has been reported, the most showed only perinuclear localization. The nuclear delivery is fundamental when DNA Derivatized NDs bind to the target antigen immobilized on Sepharose 6B matrix through antibody-antigen interaction [34] is the loaded material. 20 In an interesting study Perevedentseva et al 31 compare NDs internalization in human cancer and non-cancer cells.…”
Section: Cell Interaction Studies and Cellmentioning
confidence: 99%